Регулирующие механизмы аромокоррекции - М. А. Карапетян; Н. Ю. Адамян (ՀՀ ԳԱԱ հրատ.)
Փորձարարական մեթոդով պարզաբանվել են շնչառական համակարգի տարբեր խանգարումների ժամանակ օգտագործվող հոտավետ նյութերի շտկող ազդեցության կարգավորիչ մեխանիզմները: Տարբեր հիվանդությունների ժամանակ նկատվող շնչառության հաճախության ավելացումն (տախիպնոե) ու նվազումը (բրադիպնոե) մոդելավորվել է լաբորատորային ճնշախցում` օդի դուրս մղման միջոցով: The article aims to analyze the influence of aromatic substances on respiration. Aromocorrection has been studied during different stages of functional activity of respiration. The regulatory mechanisms of the corrective influence of aromatic substances in different functional disorders of organism were discovered. Different respiratory frequencies (tachipnoe, bradipnoe) were modeled in conditions of altitude chamber induced hypoxia.
Keywords: Medicine; Pulmonology